Does Surgery for Concomitant Cruciate and Meniscus Injuries Increase or Decrease Subsequent Comorbidities at 2 Years? - Cook, Chad E.; Zhou, Liang; Bolognesi, Michael; Sheean, Andrew J.; Barlow, Brian T.; Rhon, Daniel I. (The Journal of Knee Surgery, 2022)
Concomitant cruciate and meniscus injuries of the knee are generally associated with acute trauma and commonly treated with surgical intervention. Comorbidities (simultaneous presence of two or more medical conditions) may be acquired from changes in activity levels and lifestyle after an injury and/or treatment. This study aimed to compare differences in comorbidity proportions between surgical and nonsurgical approaches in Military Health System beneficiaries who had concurrent cruciate and meniscus injuries. The retrospective case control design included 36-month data that were analyzed to reflect 12 months prior to injury/surgery and 24 months after injury/surgery. A comparison of differences within and between groups in surgical and nonsurgical approaches was calculated and logistic regression was used to determine if surgery increased or decreased the odds of comorbidities at 24 months. In our sample of 2,438 individuals with concurrent meniscus and cruciate injury, 79.1% (n = 1,927) received surgical intervention and 20.9% (n = 511) elected for nonoperative management. All comorbidities demonstrated significant within-group differences from pre- to postsurgery for those with a surgical intervention; approximately, half the comorbidities increased (i.e., concussion or traumatic brain injury, insomnia, other sleep disorders, anxiety, posttraumatic stress disorder, and tobacco abuse disorder), whereas the other half decreased (i.e., chronic pain, apnea, cardiovascular disease, metabolic syndrome, mental health other, depression, and substance abuse disorders). The odds of acquiring a comorbid diagnosis after surgery reflected the bivariate comparisons with half increasing and half decreasing in odds. To our knowledge, this is the first study to explore comorbidity changes with a control group for individuals with concurrent meniscus and cruciate injuries.
Keywords: surgery; military; injury; knee; cruciate ligament; meniscus